CULTURAL AND PRAGMATICAL ASPECT OF ADVERTISING - E.S. SHABAY (Advanced Engineering Research, 2007)
This article provides the analysis of the concept of «sign», gives an overview of main characteristics of «semiosphere», pointes out the ground of misunderstanding of cross-cultural adds; detenmines the types of signes and thein connection.